COMPLIANCE MEDICATION OF HYPERTENSION - Amanda Amelia; Evita Muslimah Isnanda Putri (Program Studi Keperawatan, Fakultas Ilmu Kesehatan, ITSK RS dr Soepraoen, 2024)
Introduction The problem of hypertension has become a hot topic of discussion and has become one of the priority health problems in Indonesia and in the world, because hypertension is the most common cause of cardiovascular events. Hypertension is also referred to as the